Investigation on the role of aerosols on precipitation enhancement over Kerala during August 2018. (15th June 2022) - Jasmine, M.K.; Aloysius, Marina; Jayaprakash, Reethu; Fathima, C.P.; Prijith, S.S.; Mohan, Mannil
Abstract: Previous studies based on satellite data and model analysis have shown that the dust over Arabian Sea correlates positively with the Indian summer monsoon. During August 2018, over a period of a few days from August 13, the state of Kerala experienced anomalous rainfall, which was followed by heavy floods. In the present study, the meteorological factors and the aerosol conditions during this event are investigated. MERRA 2 reanalysis data suggests that the dust loading over the Arabian Sea during the month of August, during which the anomalous event of rainfall took place, is the highest in the last decade. Using CALIPSO aerosol vertical profiles, OMI Absorbing Aerosol Index and the HYSPLIT back trajectory analysis, higher altitude dust transport from the arid gulf region towards the Arabian sea and near to Kerala coast is confirmed during the heavy precipitation days and even prior to that. Changes in cloud properties like Cloud Fraction (CF), Cloud Top Temperature (CTT), Cloud Water Liquid Water Path (CWLWP) and Cloud Condensation Nuclei (CCN) with AOD variations during the period clearly indicate that there is a close relation between the aerosols and the cloud properties over the region. Observed CWLWP in the study on August 14 and 15, 2018 was 80% higher than the monthly average value. CCN concentration was increased by 23 percent during the severe rainy days of August when the CTT was about 16 K lower than the monthly mean value. Dust aerosols at altitudes of 2–4 km and further higher at 10–15 km, along with the deep convective clouds, point to the possibility of aerosol-cloud-precipitation interaction under conducive meteorological conditions. INSAT- 3D temperature profiles show an interesting enhancement of temperature (∼1 K) at altitudes ∼ 3 km, where elevated dust layers are noticed. This elevated heating could pave the way for moisture convergence and it is further confirmed from the INSAT derived Relative Humidity profiles. Investigation of vertical winds shows strong updrafts over the region during the period of heavy precipitation, indicative of the coexistence of moisture and CCN at higher altitudes. The study infers that the moisture built up over the region was excessive, enough to overwhelm the commonly observed semi direct effect caused by aerosols, and in contradiction, the aerosols amplify the cloud cover and precipitation over the Kerala region during the period of study. Thus the heavy dust loading over the South Eastern Arabian Sea region, near the west coast of Kerala, together with the conducive meteorological conditions and orography of the region led to intensified precipitation over Kerala during the mid of August 2018. Highlights: The aerosol loading near the Kerala region during 14–17 August 2018 was found to enhance the precipitation over the state. Heavy dust loading from the West Asia Regions and enhanced moisture convergence over the Kerala region supported the rain cloud formation over the region. Aerosol-cloud-precipitation interaction found to contribute to the heavy rains of August 2018 over Kerala.